Annual Report of the Congressional Research Service of the Library of Congress for Fiscal Year 2014 (Congressional Research Service (CRS), 2015)
Toàn văn báo cáo thường niên của Dịch vụ nghiên cứu Quốc hội của Thư viện Quốc hội Mỹ cho năm tài chính 2014.